Strategi Keberlanjutan di LPD Desa Adat Tulikup Kelod - Ni Made Ayu Kurnia Sari; I Wayan Sudiana; I Putu Fery Karyada (UNHI Press, 2026)
This study aims to analyze the sustainability strategies implemented by LPD Desa Adat Tulikup Kelod in addressing an acute liquidity crisis and fraud. The institution was on the brink of bankruptcy with a cash ratio of 0.22% and financial irregularities reaching IDR 15.6 billion. A descriptive qualitative method was employed, using in-depth interviews with the the traditional leader of the village (Bendesa Adat), the Chairperson of the PAS Team, and the Acting Chairperson of the LPD. Data were analyzed using the Miles and Huberman model with source triangulation. The results reveal that the sustainability strategy was an autonomous intervention by the Traditional Village through the formation of the PAS Team (Recovery, Audit, and Solution). Utilizing the “Focus on Solution” paradigm and “Strategy × Execution = Result” model, the team executed comprehensive restructuring. Short-term strategies focused on immediate recovery through investigative audits and aggressive debt collection, while long-term strategies emphasized governance transformation and risk mitigation. The study concludes that institutional sustainability is rooted in social legitimacy restoration and the integration of managerial, financial, and socio-cultural aspects. This intervention successfully restored the LPD's resilience, achieving a real profit of IDR 1.4 billion by 2022.